Neuroligin-3 and neuroligin-4X form nanoscopic clusters and regulate growth cone organization and size. Issue 5 (20th September 2021) - Gatford, Nicholas J F; Deans, P J Michael; Duarte, Rodrigo R R; Chennell, George; Sellers, Katherine J; Raval, Pooja; Srivastava, Deepak P
Abstract: The cell-adhesion proteins neuroligin-3 and neuroligin-4X (NLGN3/4X) have well described roles in synapse formation. NLGN3/4X are also expressed highly during neurodevelopment. However, the role these proteins play during this period is unknown. Here we show that NLGN3/4X localized to the leading edge of growth cones where it promoted neuritogenesis in immature human neurons. Super-resolution microscopy revealed that NLGN3/4X clustering induced growth cone enlargement and influenced actin filament organization. Critically, these morphological effects were not induced by autism spectrum disorder (ASD)-associated NLGN3/4X variants. Finally, actin regulators p21-activated kinase 1 and cofilin were found to be activated by NLGN3/4X and involved in mediating the effects of these adhesion proteins on actin filaments, growth cones and neuritogenesis. These data reveal a novel role for NLGN3 and NLGN4X in the development of neuronal architecture, which may be altered in the presence of ASD-associated variants.